THE SECOND HANKEL DETERMINANT FOR A CLASS OF SPIRALLIKE FUNCTIONS DEFINED BY HOHLOV OPERATOR - S. M. PATIL AND S. M. KHAIRNAR (International Journal of Emerging Trends in Science and Technology, 2017)
By making use of the Hohlov operator given by the class of Spirallike functions is introduced. The object of the present paper is to obtain sharp upper bound for functional |a2a4 − a 2 3 |.